LAGU SEBAGAI MEDIA PEMBELAJARAN FONOLOGI PADA SISWA MI MUHAMMADIYAH TRUKAN - Adella Nur Azizah; Aninditya Sri Nugraheni (Faculty of Languages and Arts, Universitas Negeri Padang, 2020)
The purpose of this study was to introduce and utilize the basic phonological concepts in singing to students from MI Muhammadiyah Trukan. The song used as the subject of research was Burung Kakak Tua (the Parrot) written by R.C Hardjosubroto and sings the alphabet letters from letters A to Z. The children were asked to analyze the language sounds produced by the speech tool. This research uses a direct observation method because this research focuses on real life conditions as the source of the data. The results of this study are: children have a better understanding of how sounds come out of human speech and are able to pronounce and distinguish vowels and consonants correctly and correctly.